The Influence of Career Development and Compensation to Stimulate Motivation and the Impact on Performance of Venture Capital Officers PT PNM Venture Capital Representative Office - Agus Hanafiah Darmadinata (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to determine the effect of career development on work motivation, compensation on work motivation, work motivation on performance, career development on performance, compensation on performance, career development on performance through motivation, compensation on performance through motivation. The research method used is the research method with a quantitative approach focussed on VCO position using the SmartPLS to process data. The results of this study are that career development has a positive and significant effect on work motivation, compensation has a positive and significant effect on work motivation, motivation has a positive and significant effect on performance, career development does not have a positive and significant effect on performance, compensation does not have a positive and significant effect on performance, career development has a positive and significant effect on performance through work motivation, and compensation has a positive and significant effect on performance through work motivation